Ex uno plures – Defining different types of very large rivers in Europe to foster solid aquatic bio-assessment. (December 2019) - Borgwardt, Florian; Leitner, Patrick; Graf, Wolfram; Birk, Sebastian
Highlights: We created a comprehensive abiotic characterization of very large rivers. We identified seven distinct very large river types across Europe. The very large river types were validated by macroinvertebrate sampling data. The very large river types provide a solid basis to develop bio-assessment systems. Abstract: The sustainable management of very large rivers is based on the assessment of their environmental condition. However, unlike for smaller rivers, this assessment is yet less advanced due to the specific complexities of very large river systems. In Europe, this is reflected by the lack of an international large river typology classifying these ecosystems into units with homogenous environmental features. Focussing on European rivers of >10, 000 km 2 catchment size, we collated datasets describing orographic, geological, geomorphological, hydrological and climatic features of the riverine environment. These rivers were divided into segments of about 30 km length, and 40 environmental descriptors hardly modifiable by human activities were allocated to each segment. In a subsequent cluster analysis, we identified seven large river types (LRTs) across Europe: Alpine-Influenced rivers; Baltic rivers; Central Lowland rivers; Continental Lowland rivers; Mediterranean rivers; Nordic rivers; Atlantic rivers. These LRTs were compared with existing European bio-geographical classifications and tested using contemporary river sampling data of benthic invertebrates. Our study describes a systematic pan-European typology characterising different types of European very large rivers, reviewed and validated by biological data. This typology represents an essential step in fostering the implementation of bio-assessment methods tailored to very large rivers in Europe.